IMPLEMENTASI KARAKTER DISIPLIN DAN TANGGUNG JAWAB MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP IT ISHLAHUL UMMAH KOTA TASIKMALAYA - Nurwanti Mardiyanti; Jani Sanjari (Program Studi Pendidikan Agama Islam, 2025)
This study aims to describe the implementation of the character values of discipline and responsibility among students through Islamic Religious Education (PAI) learning at SMP IT Ishlahul Ummah, Tasikmalaya. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation, and subsequently analyzed descriptively to portray the learning practices and their dynamics. The findings reveal that the internalization of discipline and responsibility is carried out through teacher role modeling, habituation of religious activities both at school and in the dormitory, as well as the integration of character values into PAI teaching materials and learning activities. The main supporting factors include the religious school environment and the active involvement of teachers in student guidance, while the challenges consist of limited parental involvement and inconsistency in program implementation. Based on these results, it can be concluded that PAI learning at SMP IT Ishlahul Ummah contributes positively to shaping students’ discipline and responsibility, although greater consistency in program implementation and stronger collaboration with parents are required to ensure more effective and sustainable character development